Advancing the WEFE nexus: Expert insights on implementation and challenges - Nikolaos Mellios; Maria Vrachioli; Georgia Tseva; Bettina Renner; Chrysaida-Aliki Papadopoulou; Giannis Adamos; Chrysi Laspidou (PLoS ONE, 2026)
This paper builds on the Water-Energy-Food-Ecosystems (WEFE) nexus approach through insights gleaned from interviews with project coordinators involved in nexus-oriented research and initiatives. By employing a structured interview format, empirical evidence highlighting the perspectives of experts on the methodologies, practices, and challenges within the nexus framework was gathered. The findings indicate that, despite growing understanding of the complexities of the WEFE nexus, its translation into practice remains limited across many project contexts. Interview participants emphasized the importance of recognizing the interdependencies among water, energy, food, and ecosystems to enhance resource efficiency and resilience against climate change. Key opportunities identified include the development of innovative technologies and nexus-specific indicators aimed at improving nexus understanding, fostering stakeholder engagement, and supporting collaborative decision-making. The study also identified pressing challenges, such as data availability, methodological alignment, and the integration of nexus activities with broader policy frameworks. Overall, the analysis examines how the WEFE nexus is conceptualized and operationalized in practice, and how analytical and governance-related challenges shape its implementation in European research and innovation projects. The insights gained from this research underscore the need for enhanced governance, effective communication, and strategic collaboration among stakeholders to capitalize on the full potential of the WEFE nexus. This paper contributes to the discourse on integrated resource management by providing a real-world perspective on the application, efficacy, and impact of the WEFE nexus framework, thereby enriching the existing knowledge stock on sustainable resource utilization.